2013
DOI: 10.1007/978-3-642-34197-7_26
|View full text |Cite
|
Sign up to set email alerts
|

Novel Concepts of “Niche-Relief” and “Niche-Voltage” for Stem Cells as a Base of Bone and Hematopoietic Tissues Biomimetic Engineering

Abstract: -An affect of relief features and quantitative variables of artificial surfaces on structural-functional status of human lung prenatal stromal cells (HLPSC) and remodeling of Balb/c mice bone/bone marrow system have been studied. Implants with rough (Ra>2 μm) calcium phosphate micro-arc coatings have structural-functional sites (micro-regions) named "niches-relief" which are necessary for maturation and differentiation of HLPSC into secreting osteoblasts in shortterm culture. Maximal remodeling of mouse bone/b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Sammons et al [ 48 ] noted that the surface roughness could be varied in the full range from nano- to microscopic scales positively impact the biological interaction between the implant and bone tissue, as it has the same order of values as cells and large biomolecules. At the same time, in [ 49 ] it has been shown that microporous biocoatings’ surfaces with the roughness of 2.5 µm < Ra < 5.0 µm promote successful stromal stem cell’s adhesion, proliferation, and differentiation into the bone tissue. However, in [ 50 ], the authors point out that the surface of implants with nano-roughness is more applicable as it promotes the adhesion of osteoblastic cells, intensifies cells’ functions (alkaline phosphatase synthesis, calcium deposition, and collagen secretion) and prevents the growth of “competitive” fibroblast cells.…”
Section: Resultsmentioning
confidence: 99%
“…Sammons et al [ 48 ] noted that the surface roughness could be varied in the full range from nano- to microscopic scales positively impact the biological interaction between the implant and bone tissue, as it has the same order of values as cells and large biomolecules. At the same time, in [ 49 ] it has been shown that microporous biocoatings’ surfaces with the roughness of 2.5 µm < Ra < 5.0 µm promote successful stromal stem cell’s adhesion, proliferation, and differentiation into the bone tissue. However, in [ 50 ], the authors point out that the surface of implants with nano-roughness is more applicable as it promotes the adhesion of osteoblastic cells, intensifies cells’ functions (alkaline phosphatase synthesis, calcium deposition, and collagen secretion) and prevents the growth of “competitive” fibroblast cells.…”
Section: Resultsmentioning
confidence: 99%
“…A quantitative assessment of the effect of CP microroughness on HLPSC differentiation into osteoblasts has led us to speculate that separate osteogenic microterritories for MSCs must exist in the ECM and may be reconstructed artificially [ 28 ]. The CP microrelief and electrical voltage have been proposed as key factors in the function of osteogenic niches [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microarc CP rough surfaces are capable of supporting an HLPSC 3D culture in the presence of osteogenic supplements (β-glycerophosphate, dexamethasone, and ascorbic acid) [ 28 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations